(untitled) (Plant Tissue Culture and Biotechnology, 2025)
An efficient procedure for mass multiplication of an epiphytic medicinal orchid from Bangladesh Bulbophyllum crassipes was established by in vitro seed culture. Seeds obtained from immature pods of B. crassipes were cultured on four different types of nutrient media viz. MS, PM, modified VW and B5. The maximum percentage of seed germination (90.75 ± 0.61) was recorded on MS where various plant growth regulators (PGRs) were used either individually or in combination for secondary protocorm development and multiple shoot buds (MSBs) induction. Secondary protocorm were developed from primary protocorm on MS with BAP, Kn and NAA. The highest number of secondary protocorms (21.07 ± 0.12) were obtain from primary protocorm in MS with 1.0 mg/l Kn and 0.5 mg/l NAA. Here 1.0 mg/l BAP and 0.5 mg/l NAA showed the best performance on plant height (3.64 ± 0.07 cm). Maximum multiple shoot buds (8.40 ± 0.26) per single shoot were developed on MS with 1.0 mg/l BAP and 0.5 mg/l NAA. For root induction single shoots were sub-cultured on ½ MS supplemented with NAA, IAA and IBA. Maximum root induction (6.50 ± 0.29) and its growth (4.11 ± 0.08 cm) was observed on ½ MS supplemented with 1.0 mg/l IAA. The well rooted plantlets were acclimatized and successfully transferred to pot containing coconut husk, brick pieces and charcoal at a ratio of 2:1:1 for further growth and development. Plant Tissue Cult. & Biotech. 34(2): 93-104, 2024 (December)